SUBOPTIMAL VITAMIN D STATUS IN INFANTS BETWEEN 1 AND 24 MONTHS OF AGE - Nicolae Grigore; Adrian Hasegan; Maria Totan; Camelia Grigore (Amaltea Medical Publishing House, 2017)
Introduction. Vitamin D is well known for its role in calcium absorption and maintenance of healthy bones and its deficiency results in rickets. Serum 25-hydroxyVitamin D (25(OH) D) is the most abundant Vitamin D metabolite and its concentration reflects Vitamin D status in humans. The aim of this study was to analyse the level of 25(OH) D in children between 1 month and 24 months of age, admitted in Sibiu Children's Hospital, with various pathologies, and to give scientific evidence for the prevention and treatment of rickets. Materials and methods. We made a retrospective study on 200 children, aged between 1 month and 24 months, hospitalized in different Pediatric Departments of Sibiu Children's Hospital between 01.09.2015 and 01.11.2016, in whom we determined the level of serum 25(OH)D. The optimal level of 25(OH)D was considered to be ≥30 ng/ml; values of 25(OH) D between 20-29 ng/mL define insufficient Vitamin D and Vitamin D deficiency is characterized by levels < 20 ng/ml. Results. Overall, 111 children (55.5%), aged between 1 month and 24 months, had levels of 25 (OH) Vitamin D below 30 ng/ml, with a mean value of 28.68 ng/ml. Of these 111 patients, 87 (78%) had 25(OH)D values between 20-29 ng/ml, with a mean value of 22.61 ng/ml and only 24 children (22%) had values less 20 ng/ml, with a mean value of 17.2 ng/ml. Conclusions. Low serum 25(OH) D levels affect more than half of infants and children, aged 1 month to 24 months, suggesting that there are many children in our area who have suboptimal levels of Vitamin D and this should be a matter of concern for families with children, for medical professionals and public health authorities. Determination of 25(OH) Vitamin D is an important test for children between 1 month and 24 months of age, to be used as a starting point in efficiently preventing rickets at this age.